SISTEM PAKAR UNTUK MENDIAGNOSA JENIS PENYAKIT PADA AYAM MENGGUNAKAN METODE FORWARD CHAINING - Resdi Hadi Prayoga (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
Diagnosis Expert System Development in the Chicken is disease type of representing knowledge with this line of reasoning. The sytem is able to provide treatmentof the disease in chickens by asking the symptoms of the disease at the time of consultation.Based on the above symptoms are selected, the system will provide result in the form oftreatment. This application program faster provides information to users who needinformation about the disease in chickens compared to seeking information by reading abook. With the restriction of access rights applied to the system, the process for managingthe knowledge base and rule base only by expert. This application can be used as an initialstep for chicken breeders to pay attention to the health of the chicken in the maintenanceperiod. Inference process would lead to the conclusion, although the list is not exhaustiveselected symptoms. This expert system application using PHP programming and to it isdatabase using MySQL. Result are given is a type of disease that is found accompanied byacertain factor against the disease were found, and its treatment.